HERBAL BIO-ENHANCERS: AN INNOVATIVE CONCEPT IN CURRENT MEDICINE. (International Journal of Food and Nutritional Sciences, 2022)
The bioenhancers: Dr. Bose initially mentioned the idea in 1929. Indian scientists initially used the term “bioenhancers” in 1979 at the RRL in Jammu, now known as the Indian Institute of Integrative Medicine. The first bioenhancer, piperine was discovered in 1979. Following then, a lot of study was conducted in the area of bioenhancer development. A bioenhancer is a substance that, at the amount employed, can increase the bioavailability and bioefficacy of the medicine with which it is combined without exhibiting any usual pharmacological activity of its own. The cost of therapy has long been a key concern for poor nations. To make treatment more accessible to the general public, scientists have been working hard. Environmental modifications typically have a favorable effect on a nation’s economy by reducing the cost of prescription medication and research. When a bioavailable medicine is taken in high doses, toxicity is decreased. In addition, it gets rid of drug resistance and cuts down on treatment time in half.